Penanaman Nilai Agama Melalui Kegiatan Praktek Ibadah Bagi Anak Masyarakat Kembang Kerang Daya - Fitriatul Wahyuni; Al Kusaeri Al Kusaeri; Baiq Ayu Sukma Wardani (Participative Journal: Jurnal Pengabdian Pada Masyarakat, 2022)
Education is the most important and most important thing possessed by a child, especially reading the Qur'an which must be taught from an early age until he grows up. Family is a factor that influences children's behavior, it is not surprising that values, self-concept or personal are influenced by family and lying associations because the family is responsible for the socialization process in transmitting cultural values ​​and community values. The objectives of implementing this community service are: 1. To increase education about the importance of inculcating religious values ​​from an early age. 2. Can know the role and importance of instilling religious values. The method used in this community service is participatory action research (PAR) by going through several stages, namely preparation, implementation of activities and evaluation. This community service produces outcomes in the form of: achievement of the KKP program and program sustainability, this aims to always remind teachers by indirectly instilling religious values ​​in children. Through this community service activity, it is hoped that all teacher staff in the village of Bunga Shell Daya, especially at MI NW 2 Kemabng Kerang Daya school and PAUD Raudatussibyan Al-Mannan can optimally increase the importance of applying religious values ​​in everyday life.